Pullulan-based films impregnated with silver nanoparticles from the Fusarium culmorum strain JTW1 for potential applications in the food industry and medicine - Wypij, Magdalena; Rai, Mahendra; Zemljič, Lidija Fras; Bračič, Matej; Hribernik, Silvo; Golińska, Patrycja (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: Biopolymers, such as pullulan, a natural exopolysaccharide from Aureobasidium pullulans, and their nanocomposites are commonly used in the food, pharmaceutical, and medical industry due to their unique physical and chemical properties. Methods: Pullulan was synthesized by Aureobasidium pullulans ATCC 201253 strain. Nanocomposite films based on biosynthesized pullulan were prepared and loaded with different concentrations of silver nanoparticles (AgNPs) synthesized by Fusarium culmorum strain JTW1. AgNPs were characterized using transmission electron microscopy (TEM), Zeta potential measurements and Fourier transform infrared spectroscopy (FTIR). In turn, the produced films were subjected to physico-chemical analyses such as goniometry, UV shielding capacity, attenuated total reflection-Fourier transform infrared (ATR-FTIR) spectroscopy, scanning electron microscopy (SEM), X-Ray photoelectron spectroscopy (XPS), and for mechanical and degradation properties. The antibacterial assays of the nanoparticles and the nanocomposite films against both food-borne and reference pathogens including Listeria monocytogenes, Salmonella infantis, Salmonella enterica, Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa and Klebsiella pneumoniae were performed using standard methods. Results: AgNPs were small sized (mean 15.1 nm), spherical, with good stability and coated with protein biomolecules. The use of higher concentrations of AgNPs as an additive to pullulan films reduced their hydrophilicity and light transmission of both UV-B and UV-A lights. Moreover, the produced films showed a smooth surface. Therefore, it can be concluded that the addition of biogenic AgNPs did not change the morphology and texture of the films compared to the control film. The nanoparticles and nanocomposite films showed remarkable antibacterial activity against both food-borne and reference bacteria. The highest activity of the prepared films was observed against L. monocytogenes. Discussion: The obtained results suggest that the novel nanocomposite films prepared from biosynthesized pullulan and AgNPs can be considered in the development of medical products and in food packaging. Moreover, this is the first report on pullulan-based nanocomposites with mycogenic AgNPs for such applications.